Periorbital acquired dermal macular hyperpigmentation: A distinctive clinical entity in young adults-Observational case-control study - T Muhammed Razmi; Vishal Thakur; Keshavamurthy Vinay; Divya Aggarwal; Bishan D Radotra; Muthu Sendhil Kumaran; Davinder Parsad (Wolters Kluwer Medknow Publications, 2020)
Introduction: Acquired dermal hyperpigmentation (ADMH) presenting on periorbital region has been described as individual case reports. We tried to characterize the features of periorbital ADMH. Materials and Methods: This was a retrospective case-control study among our patients who attended the pigmentary clinic during January 2016-December 2017. Clinical, dermoscopic, and histopathological features of subjects who were recruited during the study period were prospectively evaluated. Results: Total 19 subjects (11%) were identified among 177 ADMH patients. Periorbital ADMH patients had a relatively younger age of onset (23.26 ± 11.06 vs. 36.16 ± 13.41, P < 0.001). Dermoscopy of early periorbital ADMH showed only imperceptible speckled blue-gray dots that accentuated at outer-corner creases of eyes (the "outer-corner crease sign"). Clinicopathological features and prognosis of periorbital ADMH were similar to that of ADMH per se. Conclusion: Periorbital ADMH should be considered as a differential diagnosis of periorbital hyperpigmentation in children and young adults. Outer-corner crease sign on dermoscopy may help to rule out other differentials in its early presentation.